Ignition of a turbulent flowing gaseous mixture - Ballal, Dilip R. (Cranfield University, 1973)
The basic properties of arcs in flowing ga-,es, minimum ignition energy and quenching distances are the\focal points of this research. The flow parameters turbulence, pressure, velocities, fuel-air ratio etc. are varied over a wide range to simulate high altitude relight conditions of a gas turbine combustion chamber. — It is found that a constant-power energy release in the spark gap, having an optimum duration of 60)/s, more than halved the minimum ignition energy requirements over most of the flammability range of propane-air mixtures. At large quenching distances, lengthening of discharge path by the flowing stream results in significant reduction in heat losses to the electrodes and improvements in minimum ignition energy. The large scale intensity of turbulence tends to increase the minimum ignition energy but the quenching distance is significantly affected only by intensity. In the light of the above experimental research some discussion is presented on the practical aspects of the aircraft relight problem. Finally the various theories on ignition in turbulent flowing gases have been studied and compared with the experimental results of the present work.